Inventory models for perishable items under markdown policy / Nurzahara Atika Kamaruzaman - Nurzahara Atika , Kamaruzaman (2020)
As expected, the demand for a fresh product depends on how fresh it is, therefore, it is important to take expiration date into consideration. Based on marketing and economic theory, several factors such as price, inventory level and advertisement play a crucial role in influencing the demand. Hence, we study the effect of these factors in influencing the demand in the inventory model. Since the demand for perishable product declines over time, markdown policy is offered to increase the demand and profit while reducing the inventory. Salvage value is incorporated to the deteriorating units. In this research, we extend previous works and develop three inventory models for perishable items under markdown policy. We show that the markdown policy is an appropriate strategy to sell and get rid of slow-moving or remaining inventory when the season ends and increase the annual profit. Moreover, we find the best time to offer markdown strategy. We obtain the optimum solution with the help of numerical examples. Sensitivity analysis is presented to illustrate the effectiveness of each model.